Psychometric evaluation of a nursing competence assessment tool among nursing students: a development and validation study - Huang, Sheng-Miauh; Fang, Su-Chen; Hung, Chia-Tai; Chen, Yi-Heng (BMC medical education, 2022)
Nursing competence refers to the core abilities that are required for fulfilling one's role as a nurse. A specific instrument comprehensively measuring competence among nursing students has not yet been developed. The purpose of the study was to develop and validate a nursing competence instrument for nursing students in bachelor training. A descriptive and explorative study design was used. Data were collected from students at one medical college in Taiwan in 2020 and 2021. A total of 241 nursing students participated in this study. We developed the initial instrument through systematic review, expert evaluations, and pilot versions. Its validity was then tested using confirmatory factor analysis (CFA) and criterion-related validity, while its reliability was tested using Cronbach's alpha and test-retest analysis. The final fit indexes of CFA were as follows: chi-square = 860.1 (p < 0.01), normed chi-square = 2.24, SRMR = 0.04, RMSEA = 0.07, CFI = 0.94, and TLI = 0.94. Cronbach's alpha values for the subscales observed ranged from 0.91 to 0.98. The test-retest reliability coefficient for the Nurse Competence Scale was 0.515 (n = 30, p < 0.01). The instrument exhibited acceptable psychometric properties, thereby proving itself a valuable tool for evaluating nursing students' competence at bachelor training. Further assessments of its reliability, validity, and generality from mentors' and scholars' views in different contexts and cultures are recommended.